Competition-based heart rate, training load, and time played above 85% peak heart rate in NCAA Division I women's basketball - Sanders, G. J.; Boos, B.; Rhodes, J.; Kollock, R. O.; Peacock, C. A. (The Journal of Strength and Conditioning Research, 2021)
Basketball athletes frequently engage in intensities =85% HRpeak throughout competition. Knowing the time spent competing at intensities =85% HRpeak can improve training protocols. The purpose of the study was to assess heart rate responses across 4-quarter games (N = 31) in an NCAA Division I women's basketball season. Ten female athletes were tested and monitored with heart rate-based wearable microsensor devices. Before the season, HRpeak was recorded through a peak metabolic test (VO2peak). Average (HRavg) and HRpeak were recorded for each game, and time spent in 5 heart rate zones (HRZones) were recorded: HRZone1 = 50-60% HRpeak, HRZone2 = 60-70% HRpeak, HRZone3 = 70-76% HRpeak, HRZone4 = 77-84% HRpeak, and HRZone5 = 85-100% HRpeak. Training load was calculated with the summated-heart-rate-zone model (SHRZmod). There was a main effect of position (p = 0.019) and quarter (p = 0.005) on SHRZmod and on time spent in HRZone1-5. Athletes accumulated the most time in HRZone4 and HRZone5 and in the fourth quarter, and SHRZmod was the greatest in the fourth quarter. There was no main effect for HRavg and HRpeak (p = 0.110). Athletes averaged 34.5 minutes per game competing in HRZone5 or =85% HRpeak with nearly one-third of those minutes accumulated in the fourth quarter. Although there were no differences in HRavg and HRpeak from quarter to quarter, SHRZmod increased from the first to fourth quarter. Utilizing time spent in heart rate zones and training load with SHRZmod can provide valuable information to practitioners regarding the intensity and physiological demands of competitive basketball games.